Proton reduction by a nickel complex with an internal quinoline moiety for proton relay. Issue 31 (19th July 2016) - Majee, Karunamay; Patel, Jully; Rai, Surabhi; Das, Babulal; Panda, Binata; Padhi, Sumanta Kumar
Abstract : A dicarboxamide based nickel complex with an internal quinoline moiety, acts as an active photocatalyst for proton reduction achieving 2160 turnovers. The pendant base functions for internal proton relay towards the metal center to generate H2 following a CECE (C = Chemical, E = Electrochemical) mechanistic path. Abstract : The complexNi(DQPD) (whereDQPD = deprotonated N 2, N 6 -di(quinolin-8-yl)pyridine-2, 6-dicarboxamide (DQPDH2 )) behaves as a visible light driven active catalyst to reduce protons from water when employed with the photosensitizer fluorescein (Fl) and triethylamine (TEA) as the sacrificial electron donor. The photocatalytic system shows very high activity, attaining 2160 turnovers and an initial turnover rate of 0.032 s −1 with respect to the catalyst. The proposed electrocatalytic mechanism is of the CECE type (C is a chemical step protonation and E is the electrochemical step reduction), where theNi(DQPD) catalyst undergoes rapid protonation at the non-coordinating nitrogen atom of the quinoline before undergoing reduction. The location of the pendant base is a key factor such that the N–H resulting from the protonation of the non-coordinating nitrogen atom of the quinoline is properly located to interact with the Ni–H hydride leading to heterocoupling between protons and hydrides. Theoretical calculations for the catalytic system were carried out using the density functional level of theory (DFT) and are consistent with a mechanism for catalysis in a polypyridine nickel system. This is the first report of a polypyridine based nickel catalyst where the pendant base is responsible for the internal proton relay towards the metal center through the heterocoupling between protons and hydrides to generate hydrogen.